Design and analysis of a power transmission system for 55 kW electric tractor using agricultural workload data - Seung-Min Baek; Hyeon-Ho Jeon; Wan-Soo Kim; Yeon-Soo Kim; Yong-Joo Kim (Scientific Reports)
Abstract In this study, an e-powertrain for 55 kW electric tractors was designed and analyzed using agricultural workload data. The electric tractor power transmission system structure was analyzed, and three types were selected: the single-motor, the dual-motor, and the dual-motor including a planetary gear set (PGS). The single-motor specification for type I was 62.8 kW at 199.5 Nm. In type II, the power take-off (PTO) motor specification was 55.3 kW at 176.0 Nm, and the traction motor specification was 58.4 kW at 185.3 Nm. In type III, the PTO motor specification was 55.3 kW at 176.0 Nm, and the traction motor specification was 11.8 kW at 37.7 Nm. The power and torque of the single motor of type I were the highest. In type II, both the PTO and traction motor specifications were above those of the 55.3-kW engine. In type III, the PTO motor specifications were identical to those of type II. Moreover, the adoption of the traction motor specification could significantly reduce the required output by 80% compared with that of type II. A comparison of the mechanical components by e-powertrain type showed that the number of mechanical components exhibited the descending order of type II, type III, and type I. Depending on the tractor power, the powertrain structure can be appropriately applied. This study is expected to facilitate future development and optimization of the e-powertrain.